THE CRUCIAL ROLE OF X-RAYS IN MEDICAL DECISION-MAKING: A DEEP DIVE INTO DIAGNOSTIC IMAGING - Abdullah, Al Mutairi, Sami; Abdulrahman, Al Hebs, Mohammed; Daghiman, Al Shammari, Mutaib; Naji, Al Sharari, Badr; Husayyan, Al Enazi, Fahad (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2022)
This article explores the pivotal role of X-ray imaging in medical decision-making, offering a comprehensive overview of its historical evolution, technical aspects, and contemporary applications. The initial section delves into the discovery and technological advancements of X-rays, setting the stage for understanding their significance in modern medicine. The core of the article focuses on the integral role of X-rays in diagnosis, highlighting their precision and reliability through various case studies. It examines different types of X-ray procedures, including traditional radiography and advanced computed tomography (CT) scans, elucidating their specific applications in clinical settings. Significant attention is given to the latest innovations in X-ray technology, particularly the shift towards digital imaging and its impact on diagnostic accuracy and patient care. The article also discusses the critical role of X-rays in treatment planning, from surgical preparations to monitoring ongoing treatments. Safety and risk management, especially concerning radiation exposure, are addressed comprehensively, alongside ethical and legal considerations in X-ray usage. The conclusion offers insights into future trends and potential technological advancements in X-ray imaging, suggesting a continuously evolving impact on medical protocols and patient outcomes.